Pengembangan Media Pembelajaan Fisika Berbasis Mobile Learning dengan Menggunakan Adobe Flash Cs 6 Siswa Kelas XI MAN 2 Padang - Jannah, Raudhatul (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This research aims to develop a product of physics instructinal media based on mobile learning on the subject matter of elasticity for the students of class XI Madrasah Aliyah which is valid, practical, and effective to use in learning physic. This research is a development research 4Dâ€™s model (Define, Design, Develop, Desseminate). This product have been valued by ( 1 language expert, 2 physics material expert, 2 media expert) for validity test,( 4 physics theachers of MAN 2 Padang and 36 students) for practical test and 109 students for effectiveness test. The Instrument of this research is form of a questionnaire check list. The results showed that the physics instructional media based on mobile learning is very valid with an average 92,59,Â very practical based on 4 physics theachers and 36 students of class XI MAN 2 Padang with an average 87,08 and 83,02, and effectively used based on 109 students of class XI MAN 2 Padang with an average 77,01. Based on the findings, it may be concluded that the physics instructional media based on mobile learninng with an adobe flash cs 6 is very valid,very practical, and effective used in physics learning of class XI MAN 2 Padang.